The Multi-Faceted Role of Autophagy During Animal Virus Infection - Jiang, Hui; Kan, Xianjin; Ding, Chan; Sun, Yingjie (Frontiers in Cellular and Infection Microbiology, 2022)
Autophagy is a process of degradation to maintain cellular homeostatic by lysosomes, which ensures cellular survival under various stress conditions, including nutrient deficiency, hypoxia, high temperature, and pathogenic infection. Xenophagy, a form of selective autophagy, serves as a defense mechanism against multiple intracellular pathogen types, such as viruses, bacteria, and parasites. Recent years have seen a growing list of animal viruses with autophagy machinery. Although the relationship between autophagy and human viruses has been widely summarized, little attention has been paid to the role of this cellular function in the veterinary field, especially today, with the growth of serious zoonotic diseases. The mechanisms of the same virus inducing autophagy in different species, or different viruses inducing autophagy in the same species have not been clarified. In this review, we examine the role of autophagy in important animal viral infectious diseases and discuss the regulation mechanisms of different animal viruses to provide a potential theoretical basis for therapeutic strategies, such as targets of new vaccine development or drugs, to improve industrial production in farming.